A label-free fluorescent sensor for the detection of Pb2+ and Hg2+1. Issue 15 (7th August 2015) - Xu, Hanchu; Zhan, Shenshan; Zhang, Dongwei; Xia, Bing; Zhan, Xuejia; Wang, Lumei; Zhou, Pei
<x xml:space="preserve">Abstract</x> A fluorescent sensor for the determination of Pb2+ and Hg2+ by using SYBR Green I and an integrated functional nucleic acid.